2020
DOI: 10.7575/aiac.ijels.v.8n.3p.01
|View full text |Cite
|
Sign up to set email alerts
|

Current Educational Practices from Multicultural Perspectives in Oromia Secondary Schools: Opportunities and Challenges

Abstract: The purpose of this study is to examine the current educational practices from multicultural perspective in secondary schools of Eastern Wollega Zone, Oromia, Ethiopia. To realize this, survey method was adopted to collect data from 5 experts, 10 principals, 51 teachers, and 102 students. The students were select randomly by using simple random sampling techniques while experts, principals, and teachers were selected by the availability sampling method. Questionnaires and interviews were used for data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Teachers should be trained in culturally sensitive pedagogy. Additionally, Ethnic conflicts and political interference are multifaceted difficulties encountered while implementing MCE in universities (Motuma, 2015;Debela, 2020;Dereje, 2016;Abeya and Ferew, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers should be trained in culturally sensitive pedagogy. Additionally, Ethnic conflicts and political interference are multifaceted difficulties encountered while implementing MCE in universities (Motuma, 2015;Debela, 2020;Dereje, 2016;Abeya and Ferew, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the commitment of teachers plays a vital role in multicultural curriculum implementation. Similarly, Debela (2020) reported that a multicultural curriculum programme is capable of transforming its pedagogy and evaluation approach to respond to the transformation of teachers to multicultural commitment and create possibilities and actions for social justice in multicultural setting reform.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Consequently, the delivery process of teaching and learning could be employed appropriately and effectively. Tezera [31] examined various cultural-based teaching practices through teachers' cultural diversity, which discovered that teachers were familiar with the significance of cultural diversity education. Nonetheless, several improvement areas regarding teaching skills, cultural-based instructional knowledge, and attitudes towards classroom diversity were identified.…”
Section: Literature Reviewmentioning
confidence: 99%